"Platform nine and three‐quarters" and more: Scaffolding ESL writing through teacher modelling and creative imitation. Issue 4 (22nd December 2018) - Choi, Tat Heung; Wong, Wai Ching Crystal
Abstract : This article offers an account from a preservice teacher of a 5‐year double bachelor's degree programme seeking certification for teaching English as a second language (ESL) in Hong Kong. Crystal charts her capstone experience of conducting classroom‐based writing research into one of the family of story genres—narrative—under the guidance of Choi. Her Grade 9 ESL learners were instructed to produce a written response to a prompt from the wizardry world of Harry Potter. This pedagogical intervention was motivated by a desire to scaffold the writing of ESL learners, with the longer term goal of their developing the necessary knowledge and skills required for high‐stakes examinations. The article reviews the challenges of ESL writing instruction and considers using genre pedagogy to scaffold ESL learners, moving them towards the goal of becoming builders of effective and creative narratives. The pedagogical concerns were tackled through a focus‐group interview with ESL learners, as well as the collection of evidence from selected writing samples. The article concludes that explicit writing instruction through teacher modelling and creative imitation can be an enabling and liberating experience for still‐developing ESL learners.